Saponins from Panax notoginseng ameliorate steroid resistance in lupus nephritis through regulating lymphocyte-derived exosomes in mice - Chen, Jia; Zhou, Qingyun; Lu, Ying (Frontiers in Pharmacology, 2022)
Lupus nephritis (LN) is the most common and severe type of organ damage and an important primary disease in end-stage renal failure in patients with systemic lupus erythematosus (SLE). Clinical guidelines recommend steroid treatment, but steroid resistance has become a major factor leading to treatment failure and affecting prognosis. Our previous study demonstrated that Saponins from Panax Notoginseng (Panax ginseng saponins, PNS) could reverse steroid resistance of lymphocytes by downregulating P-glycoprotein (P-gp) expression and provide renal protection in LN mice, but the mechanism by which lymphocytes transmit these related messages to renal lamina propria cells is not clear. Therefore, we further elucidated this mechanism through holistic experiments. In this study, low-dose methylprednisolone (0.8 mg/kg/day, MP) was used to induce a steroid-resistant lupus nephritis (SR-LN) mouse model in weeks one to four, and a therapeutic steroid dosage (MP 12 mg/kg/day) or a combined PNS (PNS 100 mg/kg/day) treatment was administered from week five to eight. Lymphocyte-derived exosomes (Lyme-Exos) were isolated from the spleens of mice and injected into untreated homozygous LN mice for 14 days via the tail vein. At the end of the experiment, the efficacy and mechanism of action of different groups of Lyme-Exos on LN mice were observed. The results revealed that exogenously injected Lyme-Exos were effectively taken up by the kidney and affected the progression of kidney disease. Steroid-resistant lymphocyte-derived exosomes intervented with PNS significantly downregulated the levels of silent information regulator-related enzyme 1 (Sirt1), multidrug resistance gene 1 (MDR1), and P-gp in the renal cortex and glomerular endothelial cells (GECs); reduced serum autoantibody [antinuclear antibody (ANA) and anti-double-stranded DNA (dsDNA)] levels and inflammatory markers (WBC, PCR, and PCT); improved renal function; and attenuated urinary microalbumin excretion. Additionally, renal histopathological damage (HE staining) and fibrosis (Masson staining) were improved, and immune complex (IgG) deposition and membrane attack complex (C5b-9) production were significantly reduced; the gene levels of inflammatory factors (INF-γ, MCP-1, IL-8, IL-17, vWF, VCAM-1, IL-1β, IL-6, PTX3) in the renal cortex were downregulated. Taken together, this study showed that PNS may alleviate steroid resistance in GEC by interfering with steroid-resistant Lyme-Exos to ameliorate LN progression, which will likely provide insights into developing a new LN treatment.